An efficient visible light photocatalyst based on tin porphyrin intercalated between TiO2–graphene nanosheets for inactivation of E. coli and investigation of charge transfer mechanism. Issue 29 (2nd March 2016) - Zargari, S.; Rahimi, R.; Yousefi, A.
Abstract : Tin porphyrin intercalated between the TiO2 –grphene nanocomposite. The inactivation of E. coli over the prepared compound was significantly increased via the interaction of tin porphyrin between the TiO2 –graphene nanocomposite. Abstract : Among the very few efforts for the preparation of stable pillared graphene nanostructures, there is no report of tin porphyrin intercalated between TiO2 –graphene (TG) nanosheets. Photocatalytic inactivation of bacteria mediated by TiO2 –graphene nanocomposites has been known as a green route, which has the potential to replace current antibiotic technology. In this work we intercalated a tin complex of tetrakis(4-carboxyphenyl)porphyrin (SnTCPP·Cl2 ) between TiO2 –graphene nanosheets (TGSP) with 3% graphene content (TG (3%)). All materials were thoroughly characterized by Raman, XRD, DRS, BET, and SEM analysis. Subsequently, photoelectrochemical investigation determined the photoactivity of the prepared TGSP and the mechanism of the charge transfer in this compound. Furthermore, it has been demonstrated that the incorporation of SnTCPP between the TG nanosheets could successfully develop a new type of photocatalysis system. This photocatalyst is effective for the efficient photocatalytic inactivation of bacteria under visible light illumination.